2022
DOI: 10.3389/fpsyg.2022.1011447
|View full text |Cite
|
Sign up to set email alerts
|

Do college students with future work self-salience demonstrate higher levels of career adaptability? From a dual perspective of teachers and students

Abstract: Faced with tremendous employment pressure, how to enhance effective career exploration and career adaptability is crucial for college students’ career. This study uses self-assessed data from 840 undergraduate students at three time points to reveal the formation mechanism of career adaptability from a dual perspective of teacher support and students’ effective part-time behavior. In particular, the mediating role of career exploration is introduced based on self-regulation theory, and the moderating role of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Next, we found that nursing students with part-time experience were more likely to be in the group with “high perceived professional preparedness”, which is consistent with the findings of several studies [ 15 , 16 ]. Part-time experience can help college students better adapt to their careers and demonstrate a greater appreciation for developing positive psychological capital [ 51 ]. Studies on nursing students have also shown that nursing students with part-time experience have higher career adaptability than those without such experience [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we found that nursing students with part-time experience were more likely to be in the group with “high perceived professional preparedness”, which is consistent with the findings of several studies [ 15 , 16 ]. Part-time experience can help college students better adapt to their careers and demonstrate a greater appreciation for developing positive psychological capital [ 51 ]. Studies on nursing students have also shown that nursing students with part-time experience have higher career adaptability than those without such experience [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to self-determination theory, the future work self serves as a motivational career resource that can motivate students to engage in current goal-setting and goal-striving behaviors to achieve a desired future [ 22 , 39 ]. Students who have a higher level of salience and elaboration about their future work self can not only clearly depict the image of their future work [ 40 ] but also take the initiative to learn job-related knowledge and skills needed in career development [ 12 ] to purposefully enhance a series of comprehensive abilities and strengthen their employability [ 41 ]. It follows that the future work self plays a motivating role in increasing students’ perceived employability.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It has been identified that career calling positively correlated with career adaptability [14]. Career adaptability, a multidimensional psychosocial construct linked to an individual's long-term career success, is the ability to handle career development-related tasks using available resources [55][56][57]. A survey based on Chinese pre-service female primary school teachers found that greater career adaptability was associated with higher individual perceptions of future decent work and higher academic satisfaction [53].…”
Section: The Chain Mediating Role Of Career Adaptability and Decent Workmentioning
confidence: 99%